Teacher Teaching Model and Impact on Student Learning Motivation At SMP Negeri 4 Bolaang Mongondow Utara - Septriana Dewi; Kartin Lihawa; Sri Rumiyatiningsih Luwiti (Transbahasa, 2024)
This study aims to identify the teaching models frequently used by teachers and how teachers motivate students to learn English at SMP Negeri 4 Bolaang Mongondow Utara. The research method is qualitative, employing a data collection approach that includes observation, interviews, and documentation. The participants in this study were one English teacher and 28 eighth-grade students of SMP Negeri 4 Bolaang Mongondow Utara. The data analysis conducted by Satori and Komariah involves data reduction, data presentation, and conclusion drawing. The results of this study indicate that the contextual teaching and learning (CTL) strategies employed by the instructor at this school enhance student participation and enthusiasm for learning. Student motivation was categorized into three levels: low, medium, and high. Students with low motivation complained about the amount of memorization and assignments required and struggled to understand the material. They were less engaged in class and expressed dissatisfaction with their educational experiences. Despite challenges such as language difficulties and pronunciation issues, students with medium motivation maintained a relatively high level of motivation. They stayed engaged in class, particularly during ice-breaking activities that helped keep them motivated. Highly motivated students enjoyed the learning process and were driven by an engaging learning environment and admiration for their teacher. Students responded positively to educational strategies that could be applied to their lives.